Consuls and Captives : Dutch-North African Diplomacy in the Early Modern Mediterranean - Heinsen-Roach, Erica (Book collections on Project MUSE., 2019)
"Analyzes how negotiations between Dutch consuls and North African rulers over the liberation of Dutch sailors helped create a new diplomatic order in the western Mediterranean"--